Cultivation of microalgae on food waste: Recent advances and way forward. (November 2022) - Kumar, Yogesh; Kaur, Samandeep; Kheto, Ankan; Munshi, Mohona; Sarkar, Ayan; Om Pandey, Hari; Tarafdar, Ayon; Sindhu, Raveendran; Sirohi, Ranjna
Graphical abstract: Highlights: Cultivation of microalgae on food processing waste has been discussed. Standardization of culture conditions can sustain cultivation of desired strains. Processing of large volumes of water is required to harvest microalgae biomass. Pretreatment of microalgal biomass increases the biomass yield. Investigation on techno-economic feasibility and waste supply chain is required. Abstract: Microalgae are photosynthetic microbes that can synthesize compounds of therapeutic potential with wide applications in the food, bioprocessing and pharmaceutical sector. Recent research advances have therefore, focused on finding suitable economic substrates for the sustainable cultivation of microalgae. Among such substrates, food derived waste specifically from the starch, meat, dairy, brewery, oil and fruit and vegetable processing industries has gained popularity but poses numerous challenges. Pretreatment, dilution of waste water supernatants, mixing of different food waste streams, utilizing two-stage cultivation and other biorefinery approaches have been intensively explored for multifold improvement in microalgal biomass recovery from food waste. This review discusses the advances and challenges associated with cultivation of microalgae on food waste. The review suggests that there is a need to standardize different waste substrates in terms of general composition, genetically engineered microalgal strains, tackling process scalability issues, controlling wastewater toxicity and establishing a waste transportation chain.